A multicenter, propensity score-matched analysis of functional outcomes and recanalization success with or without Trevo for Medium and distal vessel occlusion - Siegler, James E.; Möhlenbruch, Markus Alfred (Interventional neuroradiology, 2025)
Background - Endovascular therapy (EVT) for stroke due to distal or medium vessel occlusion (DMVO) is safe. Due to the distinct anatomical characteristics of DMVOs, further evaluation of EVT is crucial to determine which devices may yield better outcomes. - Methods - A retrospective analysis of adults with DMVO treated in 37 centers (11 countries) was queried. The primary outcome of favorable shift in 90-day modified Rankin Scale (mRS) was compared between patients treated with Trevo versus other devices on first pass using 1:1 propensity score matching (PSM) with multivariable adjustment. Secondary outcomes included the number of pass attempts, final thrombolysis in cerebral infarction (TICI) score 2b-3, symptomatic intracranial hemorrhage (sICH), improvement in National Institutes of Health Stroke Scale (NIHSS) at 24h, and 90-day mortality. - Results - Of the 1115 included patients, 264 (24%) were treated with Trevo (PSM cohort of 261 per group). Trevo use was not associated with a favorable 90-day mRS shift (proportional odds ratio [OR] 1.10, 95% confidence interval [CI] 0.80-1.51). Trevo was associated with fewer passes (adjusted β=-0.25, 95% CI −0.48 - −0.03), higher odds of TICI 2b-3 (adjusted OR 1.97, 95% CI 1.11-3.49), and a greater 24h NIHSS improvement (adjusted β= −1.74, 95% CI −3.11 - −0.36), with no difference in sICH or mortality (p>0.05). Results were similar in sensitivity analyses. - Conclusions - We observed no safety concerns with Trevo as compared to other EVT devices for DMVO recanalization. There was a signal of better technical efficacy and early clinical improvement.